Fine‐needle aspiration biopsy of secondary neoplasms of the thyroid gland: A multi‐institutional study of 62 cases. Issue 1 (4th November 2014) - Pusztaszeri, Marc; Wang, He; Cibas, Edmund S.; Powers, Celeste N.; Bongiovanni, Massimo; Ali, Syed; Khurana, Kamal K.; Michaels, Paul J.; Faquin, William C.
Abstract : BACKGROUND: Secondary neoplasms of the thyroid gland (SNTGs) are uncommon, and it is important to recognize them in thyroid fine‐needle aspiration biopsy (FNAB). METHODS: The authors report a cohort of 62 SNTGs from 7 institutions in the United States and Europe. Patients were identified retrospectively by searching through medical records of the respective institutions. All initial diagnoses were rendered by FNAB. RESULTS: SNTGs represented 0.16% of all thyroid FNABs and were more frequent among women (ratio of women to men, 1.2:1.0). The mean patient age was of 59 years (range, 7‐84 years), the mean tumor size was 3 cm (range, 0.9‐7 cm), and the mean interval from diagnosis of the primary tumor was 45 months (range, 0‐156 months). Eighty‐seven percent of SNTGs were diagnosed as malignant by FNAB, and there was a specific SNTG diagnosis in 93% of patients. Immunocytochemistry and flow cytometry, which were used in 30% of patients, were useful ancillary studies. Adenocarcinomas (n = 23; 37%) and squamous cell carcinomas (SCCs) (n = 22; 35.5%) represented the majority of SNTGs, followed by lymphoma (n = 5; 8%), melanoma (n = 5; 8%), adenoid cystic carcinoma (n = 3; 5%), and various sarcomas (n = 3; 5%). Adenocarcinomas originated from the kidney (n = 9; 39%), lung (n = 6; 26%), breast (n = 5; 22%), and colon (n = 3; 13%). SCCs originated mostly from the head and neck (n = 13; 59%), followed by lung (n = 3; 13%), esophagus (n = 3; 14%), and unknown primary sites (n = 3; 14%). CONCLUSIONS: Adenocarcinomas from the kidney, lung, breast, and colon along with SCCs represent the majority of SNTGs. The current results indicate that FNAB is a sensitive and accurate method for diagnosing SNTG; however, diagnostic difficulties can occur. Knowledge of clinical history and the judicious application of ancillary studies can increase the sensitivity and accuracy of FNAB for detecting SNTGs. Cancer (Cancer Cytopathol) 2015;123:19–29 . © 2014 American Cancer Society . Abstract : Adenocarcinomas from the kidney, lung, breast, and colon along with squamous cell carcinomas represent the majority of secondary neoplasms of the thyroid gland (SNTGs). Fine‐needle aspiration biopsy is a sensitive and accurate method for diagnosing SNTGs; however, diagnostic difficulties can occur, and knowledge of clinical history and judicious application of ancillary studies can increase the sensitivity and accuracy of fine‐needle aspiration biopsy for detecting SNTGs.